The Role of Mentors in Increasing Motivation to Learn Al-Qur'an for Worshipers of Bustanul Qur'an Village Tumbang Manggu Katingan District - Miptahudin, Muhammad; Supriadi, Supriadi; Syarif, Ahmad (Al-Mudarris, 2025)
Majelis Taklim Bustanul Qur'an Tumbang Manggu Village, Katingan Regency is a forum for worshipers in studying various kinds of Islamic religious knowledge, one of which is knowledge in reading the Qur'an for adult worshipers. The need for mentors to provide motivation in reading the Qur'an, especially for adult worshipers, is very important, as happened in the Majelis Taklim Bustanul Qur'an Tumbang Manggu Katingan Regency. This is very necessary because the worshipers are adults, so tenacious and patient guidance is needed considering the difficulty of learning the Qur'an in adulthood.This research was conducted at the Bustanul Qur'an Taklim Assembly, Tumbang Manggu Village, Katingan Regency. The formulation of the problem in this study is how is the motivation to learn the Qur'an at Majelis Taklim Bustanul Qur'an Tumbang Manggu Village, Katingan Regency. The results of the study indicate that the role of religious guidance is very important in increasing the Motivation to Learn the Qur'an for the Jamaah, the religious guidance process begins with reciting together with the mentor then proceeds with reciting alone or privately by being listened to by the mentor and other worshipers, Taushiyah, and Questions and Answers. The method used by religious advisors is the method of congregation and question and answer. The effect of religious guidance carried out by religious mentors is an increase in devotion to Allah SWT and being able to read the Qur'an properly and correctly.